THE CONNECTION BETWEEN CROWDING AND JOB RELATED STRESS IN EMPLOYEE WHO USE ELECTRICITY TRAIN AS TRANSPORTATION - Rindina Desi; Hendro Prabowo (Jurnal Psikologi, 2006)
Electricty train is a very economical transportation and can be reached by all aspects of society inJabodetabek region. Otherwise, the condition of the train is very uncomfortable. Passengers always facethe very crowded condition to use the train and during the trip. Most passengers feel the crowding in avery bad circumstances and it caused stress. This crowding mentioned as one of many factors thatcorrelated to jov related stress in employees who use this transportation. The aim of this study is tomeasure the correlation between crowding and job related stress in employee who use electricity train astransportation. The result shows positive correlation between crowding and job related stress inemployee who use electricity train as transportation. This study also found other factors that might havebeen correlated to crowding such as the duration of the trip and the number of the station passed by thetrain.Key words: crowding, job related stress, electricity train